DEVELOPMENT OF LEARNING MATERIALS WITH SOCRATIC MODEL AT HISTORY OF PHYSICS - Suprapto, Nadi; Dwikoranto, D (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2011)
A history of physics lecture become important for the student because its knowledge will be a complement as knowledge framework from all that have and will be obtained by students. This is an optional lecture for the student of physics education by 2 credit which is programmed at even semester. Though an optional lecture, this is still very enthused by students. Pursuant to this situation hence done a research and development (R and D) to this lecture. Research done by student of Reguler Physics Education 2006. The aim of this research is to develop learning materials include Lesson Plan (GBRP and SAP), dictate, Student Worksheet (LKM), Appraisal Sheet (LP), hands out, physician pictures and poster oriented to socratic model. Then those are tried to the student. The result shows the ability of lecturer in managing study of Socrates categorize goodness. Result of management at introduction and activity of class condition shows that the category is very good, while for core activities, closure, and time management shows good enough category, from perception mean score ?3.0 every study steps. Student activity cover: listening actively, reading, doing and writing answer in LKM, discussing with lecturer, discussing between student in group, making resume, and irrelevant behavior successively are 14.50%, 13.50%, 16.50%, 27.75%, 20.75%, 7.00% and 0.00%. The biggest percentage activity is to discuss with lecturer, while smallest activity percentage is to make resume and irrelevant behavior. Enthusiasm learn student at negative and positive statement criterion, mean score to every condition of attention, relevansion, confidence, and satisfaction (ARCS) successively is 4.00, 4.05, 4.15, and 3.45 with good category with mean score for all condition are 3.91 so that student enthusiasm criterion in good category. The learning product of pretest at learning show all product indicator is not complete with complete mean 27.68%. Then after given by post test its result show complete mean equal to 81.67% and all item test is completed.Key words: Development materials learning, Socratic Model, R & D, History of Physics